2018
DOI: 10.1038/s41467-018-04498-w
|View full text |Cite
|
Sign up to set email alerts
|

Specific hippocampal representations are linked to generalized cortical representations in memory

Abstract: Memories link information about specific experiences to more general knowledge that is abstracted from and contextualizes those experiences. Hippocampal-cortical activity patterns representing features of past experience are reinstated during awake memory reactivation events, but whether representations of both specific and general features of experience are simultaneously reinstated remains unknown. We examined hippocampal and prefrontal cortical firing patterns during memory reactivation in rats performing a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 61 publications
(57 reference statements)
6
43
0
Order By: Relevance
“…Similar to CA1 (Figure 1), PFC neurons exhibited spatially and directionally selective firing, with PFC ensembles forming unique spatial representations of different trajectories on the maze for all sessions (Figure 6). We and others have shown that although PFC neurons have significantly lower spatial specificity and multi-peaked fields as compared with CA1 neurons Tang et al, 2017;Yu et al, 2018;Zielinski et al, 2019), PFC ensembles can still represent spatial location with high accuracy (Mashhoori et al, 2018;Zielinski et al, 2019). Just as in CA1, spatial-and directional-selective firing in PFC was seen across all 8 sessions starting with the first session on the track (Figures 6A and 6B).…”
Section: Coordinated Hippocampal-prefrontal Replay Selects Past-futurmentioning
confidence: 74%
See 1 more Smart Citation
“…Similar to CA1 (Figure 1), PFC neurons exhibited spatially and directionally selective firing, with PFC ensembles forming unique spatial representations of different trajectories on the maze for all sessions (Figure 6). We and others have shown that although PFC neurons have significantly lower spatial specificity and multi-peaked fields as compared with CA1 neurons Tang et al, 2017;Yu et al, 2018;Zielinski et al, 2019), PFC ensembles can still represent spatial location with high accuracy (Mashhoori et al, 2018;Zielinski et al, 2019). Just as in CA1, spatial-and directional-selective firing in PFC was seen across all 8 sessions starting with the first session on the track (Figures 6A and 6B).…”
Section: Coordinated Hippocampal-prefrontal Replay Selects Past-futurmentioning
confidence: 74%
“…one mapping between hippocampal and PFC representations Tang et al, 2017;Yu et al, 2018). Motivated by these response properties, the estimated firing rate (i.e., place field) of each place cell i, , is defined as a Gaussian tuning curve, where is the maximum firing rate of the i-th cell, is the linear position of the animal at time t,…”
Section: Model Simulations For Reactivation Analysismentioning
confidence: 99%
“…Although firing in the thalamus becomes sparse, spikes are correlated with other thalamic cells and with LFP population events in mPFC and CA1. Specifically, thalamic units were phase-locked to the delta and spindle frequency bands recorded in deep layers of mPFC, and some thalamic cells showed a strong rebound of activity following the down-state of the mPFC slow oscillation (1)(2)(3)(4). In addition, individual thalamic cells rarely contributed spikes in consecutive cycles of the spindle oscillation, but showed consistent correlations with other thalamic cells within the period of spindle cycles.…”
Section: Discussionmentioning
confidence: 91%
“…Two complementary learning systems acquire and process episodic memories in order to learn adaptive models of the world that generalize beyond specific experiences and continue to incorporate information through the lifetime of an animal [1][2][3][4] . The hippocampus can form memory traces rapidly; however, over time, interactions between the hippocampus and neocortex are thought to extract statistical regularities from the organism's daily experiences, and update neocortical models or schemas to increase their adaptive value 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Fr2, medial agranular cortex, premotor cortex, dorsomedial prefrontal cortex, and frontal 18 orienting field. With respect to navigation, published work indicates that M2 neuron firing predicts 19 upcoming navigational choices from a single environmental location 41 and that neighboring 20 prefrontal cortex sub-regions encode information related to rules for navigation as well as 21 anticipated effort and reward associated with a route [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] . Yet, whether M2 neuron firing 22 dynamics are consistent with a role transitioning a broader and spatially distributed set of 23…”
Section: Introduction 17mentioning
confidence: 99%